Physical Fitness Evaluation of Rural Junior High School Students in Physical Education Learning - Andi Ihsan (CV Lentera Cendekia Indonesia, 2026)
Introduction. Physical fitness is an important component in supporting students’ learning activities and physical development in schools. Physical Education (PE) learning plays a strategic role in improving students’ physical fitness through structured physical activities. Therefore, this study aimed to evaluate the physical fitness components of students in PE learning at SMP Negeri 2 Tombolo Pao. Methods. This study used a quantitative approach with a descriptive evaluative design. The sample consisted of 36 eighth-grade students selected using a purposive sampling technique. The instrument used was a physical fitness test consisting of a 20-meter run, sit-ups, push-ups, shuttle run, and sit-and-reach tests to measure speed, muscle strength, agility, and flexibility. Data were analyzed using descriptive statistics, including mean, standard deviation, percentage, and physical fitness category analysis using IBM SPSS Statistics. Results. The results showed that students’ physical fitness levels were generally in the good category. Speed obtained an average score of 4.21 seconds, agility 12.84 seconds, and flexibility 24.15 cm, all categorized as good. Meanwhile, abdominal and arm muscle strength were categorized as moderate, with average scores of 21.47 repetitions and 18.36 repetitions, respectively. The distribution of physical fitness levels indicated that 38.89% of students were in the good category, 30.56% in the moderate category, 13.89% in the very good category, 13.89% in the poor category, and 2.78% in the very poor category. Conclusions. PE learning contributed positively to students’ physical fitness levels; however, several components, particularly muscle strength, still require improvement through more structured and continuous physical activity programs. Therefore, Physical Education teachers are expected to develop more innovative and fitness-oriented learning models to improve students’ physical fitness comprehensively.